Railway Dynamics Analysis Using Lego Mindstorms - ABDULLAH, Mohd Azman; Ramli, Faiz Redza; Lim, Ching Sheng (2014)
In recent years, the high speed railway vehicle dynamics performances have been studied and investigated in order to determine the ride comfort of the passengers. Most of the time, these researches were involving expensive and high end technology of data logging system to record and analyze the data. In this research, a low cost data logging system (Lego Mindstorms) is used to gather the data from accelerometer and gyro during experimentation. The study about the behaviour of railway vehicle in term of roll and vibrations at three perpendicular axes during running at the curve track is performed. Actual field run of railway vehicle data collection is performed on the available high speed railway vehicle operating from Kuala Lumpur International Airport (KLIA) to the Kuala Lumpur (KL) Sentral. The route selected consists of several curves which are important to study the dynamics performance of the vehicle. The results from experiment establishes the dynamics performances of the railway vehicle in term of passengers’ ride comfort. With the availability of the data logging system and sensors, the railway vehicle dynamics performance can be analyzed and monitored for future improvement of railway vehicle service and operation.